2019
DOI: 10.3389/fnins.2019.00407
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Recurrence Analysis of the Pupil Size Fluctuations in Steady Scotopic Conditions

Abstract: Pupil size fluctuations during stationary scotopic conditions may convey information about the cortical state activity at rest. An important link between neuronal network state modulation and pupil fluctuations is the cholinergic and noradrenergic neuromodulatory tone, which is active at cortical level and in the peripheral terminals of the autonomic nervous system (ANS). This work aimed at studying the low- and high-frequency coupled oscillators in the autonomic spectrum (0–0.45 Hz) which, reportedly, drive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The complexity and temporal patterns of pupil-diameter changes reflect LC activity, sleepiness, cognitive processes, autonomic nerve activity, and psychiatric disorders (Usui and Stark, 1982 ; Schumann et al, 2015 ; Artoni et al, 2019 ; Nakamura et al, 2019 ; Piu et al, 2019 ). Sleepiness in particular decreases the temporal complexity and determinicity of pupil diameter (Piu et al, 2019 ). Nakamura et al reported that at the discrimination stage of the cognitive process, the complexity of pupil-diameter changes is reduced and pupil dilation occurs (Nakamura et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The complexity and temporal patterns of pupil-diameter changes reflect LC activity, sleepiness, cognitive processes, autonomic nerve activity, and psychiatric disorders (Usui and Stark, 1982 ; Schumann et al, 2015 ; Artoni et al, 2019 ; Nakamura et al, 2019 ; Piu et al, 2019 ). Sleepiness in particular decreases the temporal complexity and determinicity of pupil diameter (Piu et al, 2019 ). Nakamura et al reported that at the discrimination stage of the cognitive process, the complexity of pupil-diameter changes is reduced and pupil dilation occurs (Nakamura et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of evaluating complexity and symmetricity as SampEn and TranEn, respectively, requires further discussion. Conventional evaluation methods for pupil complexity and symmetricity utilize temporal standard deviation, Shannon entropy, and the difference between right and left pupil diameters (Usui and Stark, 1982 ; Poynter, 2017 ; Wahn et al, 2017 ; Piu et al, 2019 ). Moreover, Piu et al showed that the combination of complexity estimation by Shannon entropy and determinism is an effective diagnostic tool for identifying the states of neural systems (Piu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations